Navigating Academic Self-Concept via Social Comparison : The Moderating Impact of Achievement Goals Among Students - Zulfa, Amalia Fathiyah; Prasetyawati, Wuri (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to analyze the role of Achievement Goals as a moderator in the relationship between upward social comparison and academic self-concept among college students. The research method used a correlational quantitative with a cross-sectional design. Using convenience sampling, a total of 111 freshmen participants were obtained from an online questionnaire. PROCESS Model, 14 Hayes tested moderating effects across mastery and performance goals with approach-avoidance dimensions. Results showed no overall moderating effect of mastery or performance goals. However, performance-avoidance goals intensified the negative impact of upward social comparison on academic self-concept at low to moderate levels, while performance-approach and mastery goals had no significant effects. These findings suggest that students with performance-avoidance goals are more vulnerable in competitive settings, underscoring the need for targeted support to enhance academic self-concept across goal orientations.